Intellectual Capital On Firm Value Through Financial Performance - A. Ratna Sari Dewi; Gunawan Gunawan; Ahmad Firman; Ridwan Ridwan; Daniel Nemba Dambe (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This study aims to analyze the effect of intellectual capital on firm value through financial performance. This research was conducted at National Foreign Exchange Private Commercial Banks listed on the Indonesia Stock Exchange during the observation period from 2019 to 2021 and involved ten banks using a purposive sampling method. Data were analyzed using panel data regression and path analysis. The results show that human capital efficiency has a significant negative effect on financial performance; structural capital efficiency capital and employed efficiency have a significant positive effect on financial performance; human capital efficiency, capital employed efficiency, and financial performance have a significant positive effect on firm value; structural capital efficiency has a significant negative effect on firm value; human capital efficiency and capital employed efficiency have a significant negative effect on firm value through financial performance; structural capital efficiency has a significant positive effect on firm value through financial performance.